Treatment of Extensive Plaque Psoriasis and Psoriatic Arthropathy using Methotrexate in a Patient with High Serum Alkaline Phosphatase - Suad HH; Muna Mohammed El Amin; Gad Allah Modawe; Osman Elbasheer (Sudan Journal of Medical Sciences)
Background: Psoriasis is an autoimmune inflammatory, chronic, and relapsing disease of the skin, which can also present with severe joint inflammation and deformity. There are many treatment options, but the severe forms of psoriasis are treated successfully with cytotoxic and biologic therapies. Methotrexate being cheap and available in Sudan is considered a good option for patients with severe and extensive forms of psoriasis. One of the main drawbacks is hepatotoxicity. The aim of this report is to share an experience of treating the patient with oral methotrexate in the presence of a relative contraindication to this therapy.